Presentation skills training - Atwood, Christee Gabour (ASTD trainer's workshop series., 2017)
Don't Let Brilliant Ideas Get Lost in Bad Presentations. Inspiring and influencing others starts with the effective delivery of ideas. Speaker and trainer Christee Gabour Atwood designed the interactive two-day, one-day, and half-day workshops in this book with exactly that in mind. Help your training participants become confident speakers who engage and invigorate others with effective presentations and address challenges with tact and professionalism. Complete with effective training methodologies, this book helps you accelerate learning and leverage technology for maximum efficiency. Workshop programs found in this volume make planning easy and can be tailored for the unique needs of your organization. Supplemental resources are available online and include downloadable and customizable presentation slides, handouts, assessments, and tools.